Luminescence-Based Determination of Mefenamic Acid Using Sorption by Transcarpathian Clinoptilolite - Volodymyr Vasylechko; Liubomyr Shevchuk; Galyna Gryshchuk; Oksana Kostiv; Yaroslav Kalychak; Anatoliy Voloshinovskii (2024 IEEE, Riga, Latvia, 2024)
Sorption of the substance on the solid matrix is one of the effective methods to increase sensitivity and selectivity of luminescence (LM) determination. Luminescent chelates at low concentrations are not stable in solution, which limits their use in LM analysis of trace amounts of substances. Nanostructured materials that contain stable LM complexes of lanthanides (Ln) make it possible to significantly increase the LM quantum yield. However, during the synthesis of such phosphors the problems associated with the chelated Ln compounds encapsulation in the matrix often arise. The natural zeolites activated by Ln ions are such promising materials for solid-phase spectrofluorometry. These inorganic sorbents with crystal structures can include Ln ions in the cavity using exchanged reactions. These ions save their ability to react with organic ligands. The sorbates that have been created on the zeolite surface can absorb UV-Vis radiation and intensify LM. The possibility for mefenamic acid (MFA) [N-(2,3-Dimethylphenyl)anthranilic acid] LM determination using the Transcarpathion clinoptilolite (CL) as an efficient sorbent of Tb (III) was studied. MFA is a component of a common nonsteroidal anti-inflammatory drug. The samples of CL-Tb(III) with a constant Ln content are obtained via Ln ions sorption from aqueous solutions at pH8.25 on the CL in a solid phase extraction mode. The CL-Tb III) samples were precalcined at 250∘C and treated with the alkaline water-ethanol solution containing MFA. Obtained samples of the CL-Tb(III)-MFA luminophore were dried at 75∘C. For the excitation of the LM samples rays with the λ=282 nm are used. The LM intensity at 544 nm was chosen as the analytical parameter for the MFA quantitative determination. The proposed method was applied for microgram amounts of MFA determination in the model water-ethanol solution and does not require the use of toxic substances.
Визначення мефенамінової кислоти на основі люмінесценції з використанням сорбції за допомогою Закарпатського клиноптилоліту
2024 IEEE 14th International Conference Nanomaterials: Applications & Properties (NAP), Riga, Latvia, 2024, pp. 1-6
Keywords: clinoptilolite; terbium; preconcentration; sorption-luminescence determination; mefenamic acid